Analisis Optimalisasi Pemanfaatan Aset Daerah (Tanah) Untuk Meningkatkan PAD di Kabupaten Sampang - Melly Nur Qurani; Maulidah Narastri (Jurnal Riset Akuntansi, 2024)
The aim of this research is to find out and analyze the implementation of Optimizing the Utilization of Fixed Assets (Land) and to find out the supporting and inhibiting factors in its implementation. This research was carried out at the Sampang Regency Regional Revenue, Financial and Asset Management Agency (BPPKAD) using descriptive qualitative research methods. Research data sources were obtained from primary data and secondary data. Data collection techniques are carried out by conducting observations, interviews and documentation. The results of this research indicate that the implementation of management and utilization carried out by the BPPKAD of Sampang Regency is not yet optimal, this is because there are still many regional assets in the form of government-owned land that do not yet have legal ownership and there is still no grouping of assets that have potential and those that do not have the potential to be utilized so that The land cannot be utilized properly in the form of rental.